Ergonomic Risk Assessment for Laptop-Based Workers - ZAKARIA, NOR ZALIKHA NASUHA; Ezrin Hani Sukadarin (Progress in Engineering Application and Technology, 2025)
This study investigated ergonomic challenges in laptop-centric office environments, focusing on musculoskeletal discomfort and workstation deficiemcies. The research aimed to address health risk by identified key ergonomic problems and implementing evidence-based solutions. Using the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ), the RApid Office Strain Assessment (ROSA), and participatory group discussions, the study evaluated 17 participants to asssess discomfort levels, workstation risks, and gather practical input for recommendations. The finding reavealed significant musculoskeletal discomfort in the lower back (64.71%), neck (58.82%), and upper back (52.94%). Additionally, ROSA assessments categorized 58.82% of workstations as high risk, higlighting the need for immediate ergonomic interventions. Group discussions engaged employees, management, and HSE Corporate, ensuring the practicality and feasibility of proposed solutions while addressing specific workplace challenges. Key recommendations included using height-adjustable furniture, external keyboards, and mouse to improve posture, alongside ergonomic education and behavioral changes, such as applying the 20-20-20 rule to reduce eye strain. These interventions aligned with ergonomic guidelines to foster healthier and more productive work environments. This study underscored the importance of participatory approaches and data-driven solutions in mitigating health risks and improving workplace ergonomics in laptop-centric settings.